Improved Sensitivity of α-Fe(2)O(3) Nanoparticle-Decorated ZnO Nanowire Gas Sensor for CO - Lee, Jeongseok (Sensors (Basel), 2019)
A strategy for improving the sensitivity of a sensor for detecting CO and NH(3) gases is presented herein. The gas sensor was fabricated from ZnO metal oxide semiconductor nanostructures grown via a vapor–liquid–solid process and decorated with α-Fe(2)O(3) nanoparticles via a sol–gel process. The response was enhanced by the formation of an α-Fe(2)O(3)/ZnO n–n heterojunction and the growth of thinner wires. ZnO nanowires were grown on indium–tin–oxide glass electrodes using Sn as a catalyst for growth instead of Au. The structure and elemental composition were investigated using field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction. The gas sensing results indicate that the response value to 100 ppm CO was 18.8 at the optimum operating temperature of 300 °C.